iPolitics : citizens, elections, and governing in the new media era - Fox, Richard Logan; Ramos, Jennifer (Cambridge, UK. : Cambridge University Press, 2012)
'IPolitics provides a current analysis of new media's effect on politics. Politicians rely on Twitter, Facebook, and YouTube to exercise political power. Citizens around the world also use these tools to vent political frustrations, join political groups, and organize revolutions. Political activists blog to promote candidates, solicit and coordinate financial contributions, and provide opportunities for volunteers. iPolitics describes the ways in which new media innovations change how politicians and citizens engage the political arena. Most importantly, the volume emphasizes the implications of these changes for the promotion of democratic ideals. Among other things, contributors to this volume analyze whether the public's political knowledge has increased or decreased in the new media era, the role television still plays in the information universe, the effect bloggers have had on the debate and outcome of healthcare reform, and the manner in which political leaders should navigate the new media environment. While the majority of contributors examine new media and politics in the United States, the volume also provides a unique comparative perspective on this relationship using cases from abroad'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Political participation -- Technological innovations -- United States; Communication in politics -- Technological innovations -- United States; Internet in political campaigns -- United States; Mass media -- Political aspects -- United States; Internet in public administration -- United States; Internet -- Political aspects -- United States